If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 6 = 9 Reorder the terms: 6 + 2n = 9 Solving 6 + 2n = 9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2n = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 2n = 9 + -6 2n = 9 + -6 Combine like terms: 9 + -6 = 3 2n = 3 Divide each side by '2'. n = 1.5 Simplifying n = 1.5
| 6+7=5 | | 114=6k | | 8x-y=370 | | 48q-12= | | .546=.42y | | -12-3x=18-5x | | 5-(1+10)=104 | | 5[6a-2a(3a+2b)+6a^2]= | | 10w=1000 | | -12-3x=185x | | -.1035=.23n | | 0.6j=1.44 | | d-3+2=5 | | -.007h=.2002 | | 0.6=144 | | 2(4r-1)=16r+1 | | 4x+3=3+4x | | 3a^2-12a+7=0 | | -91+2x=44-3x | | 8x+4x+22+30=180 | | 5y=2x-15 | | 10r+12=2(5r+6) | | 3y+9=5+5y | | 136=8uy | | 6(-3+5x)=-288 | | (6*2)+(2x+2x)=6*2x | | 2+2v=-4 | | n-56=-22 | | 15+5x=16x-1-69 | | 13r+39= | | 2000*.75= | | 9x^2+18x+12=0 |